The Strategic Analysis of PT Bank â€œXâ€ (Persero) Tbk. Transformation : To be the most admired and progressive Financial Institution in Indonesia - Sardjono, Ardana Hendratama; Do, Anh Dung; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2012)
This Study is to capture the experience overcome problems that could ruin the Bank "x" as the largest bank in Indonesia. In 2005, transformation of Bank â€œXâ€ set up to anticipate corporate problem. Literature Review for this final project, refer to the strategy diamond and concept of Value Chain. The secondary data is chosen for Research methodology approach.Achieving the target, the Bank â€œXâ€ have articulated following vision are : committed to building long-term relationships with world-class standards of service and innovative financial solution, seek to promote a culture of performance and teamwork which attracts the best personnel, and will actively contribute to Indonesia's long-term growth by working towards the success and growth of the customers. Recommendations are : Bank â€œXâ€ focus on achieving growth of low cost deposit, in case of that has to develop wholesale transaction banking; Focus on High Yield business to generate profit; Synergies and alliances between Strategic Business Unit or Subsidiaries and full supported by support services unit; Diversified business by acquiring new line of business; and focus on ASEAN market Keywords: Bank â€œXâ€, transformation, strategy diamond, value chain,